ORGANIZATION PRINCIPLES OF PROCESS MANAGEMENT EXPORT GRAIN TRANSPORTATION - Petrik , A. V. (Problems of Informatization and Management, 2021)
The paper defines the organizational principles of managing the process of grain transportation in the case of involvement of state and commercial organizations, subject to consistent adoption of operational measures. The ways of improving the system of grain export are shown and the methodology of choosing the optimal number of vehicles for servicing agricultural enterprises is substantiated.